125k views
2 votes
-22 = 6x + 4
Hehehhe I need help agaaaaiiin

2 Answers

6 votes

Answer:

wh4t th3 0th3r p3rs0n s41d

Explanation:

h33h33h33h33h33h33h33h33hh33h3h3h3h3h333h33hhhhh333333

User Tho Nguyen
by
4.9k points
3 votes

Hey there!


Answer:\boxed{x=(-13)/(3)}


Explanation:


-22=6x+4

Let's start off with flipping the equation.


6x+4=-22

Now we need to subtract 4 from both sides of the equation.


6x+4-4=-22-4\\6x=-26

Now in our third/last step, we will divide both sides by 6.


(6x)/(6)=(-26)/(6)


x=(-13)/(3)


\boxed{x=(-13)/(3)}\text{ is the answer.}

Hope this helps!


\text{-TestedHyperr}

User Inkyu
by
5.4k points